Map of Labrador Peninsula compiled by D.I.V. Eaton drawn for photo-lithography by C.O. Senécal. - Eaton, Daniel Isaac, -1814. http://id.loc.gov/authorities/names/n50024432 http://viaf.org/viaf/sourceID/LC|n50024432; Low, A. P. (Albert Peter), 1861-1942. http://id.loc.gov/authorities/names/no00087109 http://viaf.org/viaf/sourceID/LC|no00087109; Geological Survey of Canada. http://id.loc.gov/authorities/names/n79058470 http://viaf.org/viaf/sourceID/LC|n79058470 (UM Clark Library Maps, 1896)
Geological Survey of Canada, Report by A. P. Low, Part L, Vol. viii, (New Series) p. 585-588. 1 map on 4 sheets : col. 95 x 111 cm, sheets 61 x 72 cm